2017
DOI: 10.3389/fmicb.2017.00864
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutrient Restriction on the Structure of Listeria monocytogenes Biofilm Grown in a Microfluidic System

Abstract: Biofilm formation by the pathogen Listeria monocytogenes is a major concern in food industries. The aim of this work was to elucidate the effect of nutrient limitation on both biofilm architecture and on the viability of the bacteria in microfluidic growth conditions. Biofilm formation by two L. monocytogenes strains was performed in a rich medium (BHI) and in a 10-fold diluted BHI (BHI/10) at 30°C for 24 h by using both static conditions and the microfluidic system Bioflux. In dynamic conditions, biofilms gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 54 publications
6
30
1
1
Order By: Relevance
“…Furthermore, it might play a role in bacterial migration to facilitate nutrient uptake, since the web-like pattern is most pronounced in nutrient-starved areas within the biofilm (62). This is in line with studies in Listeria monocytogenes biofilms which, under conditions of constant liquid flow, form honeycomb-like ('knitted') structures in diluted, nutrient-poor media but not in rich media (64); under static conditions, honeycomb hollows were shown to contain planktonic cells, perhaps suggesting a transition to biofilm dispersal (65). A variety of benefits from honeycomb-like structures is also supported by Schaudinn et al, who hypothesize that for cells undergoing stress from fluid forces, honeycombs could provide flexibility and distribution of forces over the six vertices (66).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, it might play a role in bacterial migration to facilitate nutrient uptake, since the web-like pattern is most pronounced in nutrient-starved areas within the biofilm (62). This is in line with studies in Listeria monocytogenes biofilms which, under conditions of constant liquid flow, form honeycomb-like ('knitted') structures in diluted, nutrient-poor media but not in rich media (64); under static conditions, honeycomb hollows were shown to contain planktonic cells, perhaps suggesting a transition to biofilm dispersal (65). A variety of benefits from honeycomb-like structures is also supported by Schaudinn et al, who hypothesize that for cells undergoing stress from fluid forces, honeycombs could provide flexibility and distribution of forces over the six vertices (66).…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that L. monocytogenes serotype 4a (Lineage III) has a strong ability to form biofilms on polystyrene [58]. Results from this work are also in agreement with findings from Cherifi et al [59] and from Di Bonaventura et al [60], who observed no differences between biofilms formed by lineages I and II. However, it must be pointed out that results obtained by different authors are very variable.…”
Section: Capacity Of Strains Of L Monocytogenes To Form Biofilmsupporting
confidence: 93%
“…The observed differences in biofilm-associated cell morphology may be due to differences in growth conditions employed in different studies. Indeed, growth conditions are important factors that have been shown to influence biofilm formation of other species (43)(44)(45). Similarly, variations in the compositions of liquid media appear to have a significant influence on H. pylori biofilm formation (20).…”
Section: Demonstration Of H Pylori Biofilms In Vitro Modelsmentioning
confidence: 99%